2020
DOI: 10.1590/2175-8239-jbn-2019-0081
|View full text |Cite
|
Sign up to set email alerts
|

Primary antiphospholipid syndrome in a hemodialysis patient with recurrent thrombosis of arteriovenous fistulas

Abstract: Introduction: The antiphospholipid syndrome is a systemic autoimmune disease defined by recurrent vascular and/or obstetrical morbidity that occurs in patients with persistent antiphospholipid antibodies. Case presentation: A patient on hemodialysis with a primary antiphospholipid syndrome presented with recurrent vascular access thrombosis, obstetrical complications, and positive lupus anticoagulant. The patient had multiple arteriovenous fistulas that failed due to thrombosis. The obstetrical morbidity was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 18 publications
(19 reference statements)
0
1
0
1
Order By: Relevance
“…Epidemiological studies have shown that [ 14 ] the incidence rate of renal disease in China is about 13%, hemodialysis is the common method to treat renal failure, and effective and well-functioning vascular access is the fundamental guarantee to perform long-term sustained hemodialysis [ 15 17 ]. Currently, AVF puncture has become the first choice to establish vascular access in the clinic because of fewer complications, high patency rate, and low cost [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…Epidemiological studies have shown that [ 14 ] the incidence rate of renal disease in China is about 13%, hemodialysis is the common method to treat renal failure, and effective and well-functioning vascular access is the fundamental guarantee to perform long-term sustained hemodialysis [ 15 17 ]. Currently, AVF puncture has become the first choice to establish vascular access in the clinic because of fewer complications, high patency rate, and low cost [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…Estudos indicam que a embolia pulmonar (EP) recorrente, bem como os achados clínicos associados à trombose, podem indicar que o paciente apresenta SAF. A EP é frequentemente acompanhada de trombose venosa profunda (TVP) das extremidades inferiores, e ambas são chamadas de tromboembolismo venoso (TEV) [7][8][9] .…”
Section: Introductionunclassified